MODEL PEMBELAJARAN TAHFIDZUL QUR’AN DENGAN INTERNALISASI NILAI NEUROSAINS - MAHDI, IMAM (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
The learning model for tafidzul Qur'an is currently in the spotlight of educational scientists in the current era, seeing the achievements and processes of the tafidzul Qur'an model only on rote learning, in this era students' needs must be critical, innovative, and creative to deal with life's problems. So this research provides neuroscience value in the thafidzul Qur'an learning model to optimize all students' brain cells. The use of research is library research in collecting literature in books, journals, and other information media. The stages of in-depth analysis begin by collecting literature, selecting, analyzing, or comparing, and drawing conclusions. The results of offering neuroscience values ​​in learning tahfidz al-Qur'an provide a new cycle in the learning process so that students achieve long-term memory, through the stages of the neuroscience-based learning process in facilitating students in memorizing the al-Qur'an and hadith